Hak Kewarisan Khuntsa Dan Cara Pembagiannya Perspektif Fiqih Dan Hukum Perdata - Muhammad Nibros Hammam; Syawaludin Syawaludin; Nabil Fikri Palasenda (Universitas Cokroaminoto Yogyakarta, 2026)
Inheritance law is regulated by religion and the state, but not all people understand it, especially in special cases such as khuntsa (intersex). This article discusses the views of fiqh and civil law on khuntsa inheritance rights and how to distribute them. This study uses a qualitative method with library research and a normative juridical approach, with the main data sources from the Qur'an, Hadith, Civil Code, and KHI. Discussion, based on the fiqh mawaris Khuntsa is divided into two types: khuntsa musykil and khuntsa ghairu musykil. The heirs who cause musykil are seven people in four jihat: the line of children, siblings, uncles, and guardianship of slaves. The inheritance share for khuntsa musykil is determined by assuming them to be male and female, then given the lowest share between the two. In the Civil Code, there are no special rules regarding inheritance for khuntsa because the share of heirs between men and women is not differentiated, only different in the group of heirs which is divided into four groups.